2020
DOI: 10.1038/s41598-020-72492-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 31P magnetic resonance spectroscopy study of mouse cerebral NAD content and redox state during neurodevelopment

Abstract: Nicotinamide adenine dinucleotide (NAD) is an important cofactor of energy-producing pathways. The redox ratio (NAD+/NADH) reflects the cellular oxidoreductive state. Oxidative stress and redox dysregulation have been suggested to contribute to various neurological diseases. The assessment of NAD content has been recently demonstrated in large animals and human brains by 31P magnetic resonance spectroscopy. However, its measurement in small rodents has never been attempted. The purpose of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Apodization with a 10 Hz exponential function was applied to all spectra prior to spectral quantification. The 31 P metabolites quantification was effectuated with a basis-set prepared with simulated 31 P spectra including PCr, α -ATP, β -ATP, γ -ATP, Pi int (intracellular inorganic phosphate), Pi ext (extracellular inorganic phosphate), PE (phophothanolamine), PC (phosphocholine), GPC (glycerophosphocholine), GPE (glycerophosphoethanolamine), MP (membrane phospholipid), NADH, NAD + , with respective linewidths 15 . Uridine diphosphate glucose (UDPG) is a phosphorylated sugar intermediate in biochemical reactions, and it contains resonances overlapping with NADH and NAD + .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apodization with a 10 Hz exponential function was applied to all spectra prior to spectral quantification. The 31 P metabolites quantification was effectuated with a basis-set prepared with simulated 31 P spectra including PCr, α -ATP, β -ATP, γ -ATP, Pi int (intracellular inorganic phosphate), Pi ext (extracellular inorganic phosphate), PE (phophothanolamine), PC (phosphocholine), GPC (glycerophosphocholine), GPE (glycerophosphoethanolamine), MP (membrane phospholipid), NADH, NAD + , with respective linewidths 15 . Uridine diphosphate glucose (UDPG) is a phosphorylated sugar intermediate in biochemical reactions, and it contains resonances overlapping with NADH and NAD + .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the low concentration of UDPG and low sensitivity in mouse brain, additional analysis was performed with summed age pooled spectra with the inclusion of UDPG in the basis-set to quantify its level and to evaluate its effect on NAD quantification results. Physiological parameters (pH int and free [Mg 2+ ] ) were calculated from chemical shift differences between 31 P metabolites (details of the calculation can be find herein 15 ).…”
Section: Spectral Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in adult Gclm − / − mice is also similar to that seen in adult patients with SZ ( Kim et al, 2017 ). MRS studies in Gclm − / − animals also found changes in ATP, phosphocreatine, intracellular pH, glutamine and glutamate, and membrane phospholipid metabolites at P20 ( Skupienski et al, 2020 ).…”
Section: Redox Biology In Psychiatrymentioning
confidence: 95%
“…Its application for the analysis of 31 P spectra with signals resonating in the spectral range of about 30 ppm is more difficult and is not often used. Recently, however, a successful modification of the input parameters of the calculation of 31 P and 13 C spectra was proposed [16,[67][68][69], which enabled the correct definition of the baseline of the spectrum. We adapted these input parameters, and we used our basis set for the analysis of 31 P spectra of muscles and the liver.…”
Section: P Basis Set For Lcmodel Calculationsmentioning
confidence: 99%